Enjoying the Festivalscape: The Effect of Festival Cues in Live-Streaming Studios on Consumers’ Intention to Stay - Ruijuan Wu; Huizhen Jin (Journal of Theoretical and Applied Electronic Commerce Research, 2025)
Live-streaming e-commerce has attracted the attention of e-retailers and consumers in recent years. However, there is a lack of evidence in understanding the influence of atmospheric stimuli of live stream on consumer engagement. This paper seeks to examine the effect of festival cues in live-streaming studios on consumers’ intention to stay in the live-streaming context. Results of four laboratory experiments indicated that presenting festival cues enhanced consumers’ intention to stay. In the relationship between festival cues and consumers’ intention to stay, festivalscape perception and pleasure–arousal played serial mediating roles. Product category moderated the effect of festival cues on consumers’ intention to stay. For non-festival products, presenting festival cues led to a stronger intention to stay. The moderating role of involvement was significant in the relationship between festival cues and intention to stay. Regarding less involved consumers, presenting festival cues significantly enhanced their intention to stay. Our work contributes to the existing knowledge of e-commerce live-streaming, festivalscape, and festival shopping, and offers relevant managerial implications for live-streaming e-retailers.